Implementation of self-instruction techniques to reduce exam anxiety in junior high school students - Mirzarisma Istighfari (Universitas Muhammadiyah Banjarmasin, 2024)
This research aimed to reduce exam anxiety using the self-instruction technique in students of SMP Muhammadiyah 1 Gresik. Anxiety often occurs before and during exams, and it can manifest in various physical, emotional, and cognitive symptoms. This study employed an experimental quantitative approach with one group pre-test and post-test design. The self-instruction technique was applied over a set period, and the effectiveness was measured using anxiety scales before and after the intervention. The results showed a significant reduction in students' anxiety levels, highlighting the positive impact of self-instruction techniques in managing exam-related anxiety.